(untitled) (London, 1983)
Major issues in the food sector; A synoptic view of the food industry; The food sector in the context of the UK economy; The economic environment of the food industry; Food and farming; Technological change in food manufacturing and distribution; Competition and performance in food manufacturing; Developments in food distribution; The role of the intermediary in the import of britain's food supplies; International aspects of food supply; A synoptic view of policy-making for the food sector; The political economy of food prices; Competition policy in the food industry; Food standards legislation as a policy instrument; The food industry and the European community; Pressures on policy formation; Food and nutrition policy - the ultimate goal; The food industry in the public interest; Economics and policy in the food industry: a summary of themes.
Keywords: Thực phẩm công nghiệp và thương mại,Food industry and trade